Effect of sintering holding time on lowtemperature degradation of yttria stabilized zirconia ceramics - Sutharsini U.; Ramesh S.; Wong Y.H.; Misran H.; Yusuf F.; Tan C.Y.; Purbolaksono J.; Teng W.D. (Maney Publishing, 2023)
Effect of sintering holding time on low-temperature degradation of 3 mol-% yttria stabilised zirconia was investigated. Yttria stabilised zirconia samples were sintered using a two-step sintering cycle. The samples were initially heated to 1500°C with the heating rate of 10°C min-1, held for 1 minute before cooling down to 1200°C and kept at this temperature for varying holding times from 0 to 10 hours. The phase contents of the zirconia samples were measured using X-ray diffractometer, and the microstructural evaluation was evaluated by field emission scanning electron microscope. All the as-sintered samples exhibited 100% tetragonal phase and bulk density of about 6 g cm-3. The low-temperature degradation study was conducted under autoclave condition containing superheated steam at 180°C and 10 bar vapour pressure for periods up to 24 hours. The results showed that the tetragonal to monoclinic phase transformation decreased with increasing holding time up to 3 hours and thereafter it increased. The sample sintered with 3-hour holding time showed better aging resistance than other samples. It was found that the grain size of this sample was the lowest (0 29 ?m) when compared to other samples. © 2014 W. S. Maney & Son Ltd.